Pengaruh Pemberian Jus Buah Naga terhadap Peningkatan Kadar Hemoglobin Ibu Hamil dengan Anemia Pada Trimester III di PMB Latibes Juliana Duren Sawit Jakarta Timur - Meri Kristina Panjaitan; Lili Anggraini (Universitas Malahayati Lampung, 2024)
ABSTRACT Anemia often occurs during pregnancy because the blood undergoes hemodilution. PMB Latibes Juliana Duren Sawit, East Jakarta, pregnant women in their third trimester who experience anemia each year have increased from 2020-2022, namely 13.6% to 15.8%. The government has tried to prevent it by giving Fe tablets and consuming foods that contain iron, one of which is dragon fruit. Knowing the effect of giving dragon fruit juice on increasing hemoglobin levels of pregnant women with anemia in the third trimester at PMB Latibes Juliana Duren Sawit, East Jakarta. Pre-experimental design with one group pretest-posttest design. The sample is pregnant women who experience anemia in April-May 2023 as many as 20 samples using a purposive sampling technique. The intervention was given 250g once a day for 14 days. Bivariate analysis using paired simple t test. The results of univariate study of Hb levels of pregnant women before administration of dragon fruit juice averaged = 10.215 gr/dl and after administration of dragon fruit juice averaged = 11.305 gr/dl. The results of the paired simple t test obtained a p value = 0.000. There is an effect of giving dragon fruit juice on increasing hemoglobin levels of pregnant women with anemia in the third trimester. Pregnant women are expected to be diligent in consuming foods that contain iron, one of which is dragon fruit juice and be obedient in consuming Fe tablets in order to increase Hb levels in the mother's blood. Keywords: Administration of Dragon Fruit Juice, Hb Levels of Anemia Pregnant Women ABSTRAK Anemia sering terjadi pada saat kehamilan karena darah mengalami hemodilusi. PMB Latibes Juliana Duren Sawit Jakarta Timur ibu hamil trimester III yang mengalami anemia setiap tahunnya mengalami peningkatan dari tahun 2020-2022 yaitu 13,6% menjadi 15,8%. Pemerintah telah berupaya untuk mencegahnya dengan adanya pemberian tablet Fe dan mengkonsumsi makanan yang mengandung zat besi, salah satunya buah naga. Mengetahui pengaruh pemberian jus buah naga terhadap peningkatan kadar hemoglobin ibu hamil dengan anemia pada trimester III di PMB Latibes Juliana Duren Sawit Jakarta Timur. Pre-eksperimental desain dengan rancangan one group pretest-posttest. Sampel adalah ibu hamil yang mengalami anemia pada bulan April-Mei tahun 2023 sebanyak 20 sampel dengan teknik purposive sampling. Intervensi diberikan 1 x sehari 250g selama 14 hari. Analisis bivariat menggunakan uji paired simple t test. Hasil penelitian univariat kadar Hb ibu hamil sebelum pemberian jus buah naga rata-rata = 10,215 gr/dl dan sesudah pemberian jus buah naga rata-rata = 11,305 gr/dl. Hasil uji paired simple t test didapatkan nilai p value = 0,000. Terdapat pengaruh pemberian jus buah naga terhadap peningkatan kadar hemoglobin ibu hamil dengan anemia pada trimester III. Ibu hamil diharapkan rajin mengkonsumsi makanan yang mengandung zat besi salah satunya jus buah naga dan patuh dalam mengkonsumsi tablet Fe agar dapat meningkatkan kadar Hb dalam darah ibu. Kata Kunci: Pemberian Jus Buah Naga, Kadar Hb Ibu Hamil Anemia